2017
DOI: 10.1111/pim.12491
|View full text |Cite
|
Sign up to set email alerts
|

Total Leishmania antigens with Poly(I:C) induce Th1 protective response

Abstract: Our proposal was to develop a vaccine based on total Leishmania antigens (TLA) adjuvanted with polyinosinic-polycytidylic acid [Poly(I:C)] able to induce a Th1 response which can provide protection against Leishmania infection. Mice were vaccinated with two doses of TLA-Poly(I:C) administered by subcutaneous route at 3-week interval. Humoral and cellular immune responses induced by the immunization were measured. The protective efficacy of the vaccine was evaluated by challenging mice with infective promastigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…Otherwise, fTLA presented a conserved protein profile with a Th1:Th2:Tr1 mixed immune response; this was also observed in our previous reports. (6) The comparison between protein integrity of pTLA and aTLA was similar to the one observed by Convit et al (13) Finally, the integrity of proteins in ultrasound and fresh extracts had a notable similarity: protein profiles were essentially unaltered. In concordance, sTLA produced a strong humoral immune response.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Otherwise, fTLA presented a conserved protein profile with a Th1:Th2:Tr1 mixed immune response; this was also observed in our previous reports. (6) The comparison between protein integrity of pTLA and aTLA was similar to the one observed by Convit et al (13) Finally, the integrity of proteins in ultrasound and fresh extracts had a notable similarity: protein profiles were essentially unaltered. In concordance, sTLA produced a strong humoral immune response.…”
Section: Discussionsupporting
confidence: 77%
“…(17) We recently reported that a synthetic double-stranded RNA TLR-3 agonist [Poly (I:C)] formulated with freezing and thawing TLA triggers a protective immune response. (6) There is a lot of evidence that demonstrates the capacity of Poly (I:C) to induce an activation of antigen presentation cells (APC), a Th1-like immune response as well as generate memory T and B cells. (18) In the present study, we evaluated the antigenic profile and the immune response generated by TLA obtained from promastigotes by cycles of freezing and thawing (fTLA), ultrasound (sTLA), autoclaving (aTLA), and pasteurisation (pTLA).…”
mentioning
confidence: 99%
“…Furthermore, all these findings confirm the importance of selecting an appropriate adjuvant for improving the immunogenicity of recombinant antigen, as well as for inducing appropriate responses in subunit vaccine that was formerly observed in the development of the RTS,S vaccine . This result with rPfTRAP antigen was consistent with other studies, implying that poly(I:C) stimulates both T‐ and B‐cell lymphocytes of Th1‐type response against viruses, Chlamydia and parasites …”
Section: Discussionsupporting
confidence: 89%
“…19 This result with rPfTRAP antigen was consistent with other studies, implying that poly(I:C) stimulates both T-and B-cell lymphocytes of Th1-type response against viruses, 75,87 Chlamydia 88 and parasites. 52,89 On day 205 of the first immunization, the percentage of reduction in IgG2a and IgG2b antibody levels in the mouse group receiving rPfTRAP-poly(I:C) as well as rPfTRAP-CFA/IFA was relatively similar, displaying the induction of long-lasting immune responses that persisted up to 205 days after the first immunization. This finding was in agreement with a previous study that found poly(I:C) in combination with PfCSP induced long-lived antibody and Th1 immune response in primates.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, all dogs showed higher production of TNF- α after stimulation with TLR3a associated with LSA when compared with medium alone and with TLR3a. Recently, the essential role of TLR3a in inducing a Th1 response as adjuvant was demonstrated in a murine model of a Leishmania amazonensis vaccine based on total antigenic extract derived from promastigotes [ 57 ]. Therefore, TLR3a demonstrated its safety and ability to induce protection and its potential for being a promising candidate for Leishmania vaccines development.…”
Section: Discussionmentioning
confidence: 99%